Judicial Discretion in Criminal Justice: Challenges, Implications, and Comparative Lessons from Indonesia and the Netherlands - Amelia, Dean Putri; Harefa, Beniharmoni (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
This article discusses the challenges and implications of applying the principle of judicial pardon rechtelijk pardon in the Indonesian legal system, by comparing similar concepts that have already been implemented in the Netherlands. This principle grants judges the discretion not to impose criminal penalties on perpetrators who are proven guilty if their actions are deemed minor, taking into account the principles of justice and humanity. This study employs a normative juridical method, utilizing a legislative, historical, conceptual, and comparative approach. The results show that the Dutch legal system has comprehensively implemented rechtelijk pardon, supported by consistent procedural law and jurisprudential practice. Conversely, the application of this principle in Indonesia still faces significant challenges due to the lack of synchronization between the substantive law in the 2023 Criminal Code and the formal law in the Criminal Procedure Code, as well as the absence of clear technical guidelines for judges to apply it. As a result, the principle of judicial pardon has the potential to become a symbolic norm without effective operationalization. This article emphasizes the importance of harmonizing the legal system and strengthening the implementation of regulations so that this principle can function optimally as an instrument of humanistic justice in national criminal law